2010
DOI: 10.1017/s0007114510003740
|View full text |Cite
|
Sign up to set email alerts
|

Hypocholesterolaemic effect of dietary inclusion of two putative probiotic bile salt hydrolase-producingLactobacillus plantarumstrains in Sprague–Dawley rats

Abstract: The purpose of the present study was to evaluate the anti-hypercholesterolaemic effects of two putative probiotic bile salt hydrolase (Bsh)-producing Lactobacillus plantarum strains, i.e. Lp91 and Lp21, in rats. L. plantarum Lp91 exhibited excellent tolerance to low pH and high bile salt concentrations as well as showed potential Bsh activity, cholesterol assimilation and cholesterol co-precipitation ability along with L. plantarum Lp21 and NCDO82 strains. Furthermore, the potential effect of L. plantarum Lp91… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
80
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(88 citation statements)
references
References 54 publications
(57 reference statements)
7
80
1
Order By: Relevance
“…Previous studies (33,34) reported that the anticholesterolemic effect of some probiotics is based on their bile salt hydrolase activity, which acts on bile salts, releasing less soluble deconjugated bile salts. These are eliminated in feces instead of being reabsorbed, leading to synthesis of new bile salts from cholesterol, which in turn decreases cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (33,34) reported that the anticholesterolemic effect of some probiotics is based on their bile salt hydrolase activity, which acts on bile salts, releasing less soluble deconjugated bile salts. These are eliminated in feces instead of being reabsorbed, leading to synthesis of new bile salts from cholesterol, which in turn decreases cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…The fermentation products generated by different lactic acid bacteria are not the same. Lee et al [14] showed variations among the respective LAB strains from kimchi, and Kumar et al [15] showed that L. plantarum Lp91 has a better effect than Lp21 in the management of hypercholesterolaemia. Thus, significant differences in the antioxidant activity and composition of fermented products can be generated by specific probiotic strains [16].…”
Section: Introductionmentioning
confidence: 99%
“…This may be related to the role of Lactobacilli in reducing the fibrinogen in blood where the consumption of probiotics can help in decreasing the level of interleukin-6 (IL-6), which in turn leads to reduction in the fibrinogen level in the blood. 34 ESR results revealed a significant increase in group C, which may be expected after increment of fibrinogen, where during the acute phase response, plasma viscosity increases as a result of the total changes in total blood protein concentration, among which is an increase of fibrinogen, which influences the ESR. 35 As for group D, the ESR result revealed a significant decrease.…”
Section: Discussionmentioning
confidence: 83%